The Effect of Rifampicin on the Induction of MDR1/P-gp Activity in Proinflammatory Human Macrophages - E. N. Pavlova; M. V. Erokhina; E. Yu. Rybalkina; D. M. Potashnikova; A. G. Masyutin; L. N. Lepekha; A. E. Ergeshov (Антибиотики и Химиотерапия)
Background. The effect on the activity of the multidrug resistance protein P-glycoprotein (P-gp, MDR1 gene) in pro-inflammatory (M1) human macrophages is considered one of the promising strategies for increasing the effectiveness of the treatment in patients with pulmonary tuberculosis: P-gp activity is considered a factor that reduces intracellular accumulation of rifampicin (RIF), a substrate for P-gp. The aim of this work was to reveal the effect of the therapeutic concentration of RIF on the activity of P-gp in M1 human macrophages. The objectives were as follows: to determine the expression levels of the MDR1 gene, P-gp protein, as well as its functional activity at different periods of cell differentiation and under the influence of RIF.Material and methods. The following cell lines were used in the work: suspension cells of promonocytic leukemia THP-1 and THP-1 macrophages induced by phorbol ether according to the pro-inflammatory phenotype. Suspension cells of myeloid leukemia K562/IS-9 transfected with the MDR1 gene were used as a comparison group. An important factor is the choice of the experimental concentration of RIF: the average concentration of the drug in patients with pulmonary tuberculosis was 10 µg/ml. The methods of RT-PCR, immunocytochemistry, and flow cytometry were used in the work.Results and discussion. The induction of MDR1 gene expression in M1 macrophages under short-term exposure to a therapeutic concentration of RIF was revealed. This effect is typical only for THP-1 macrophages, in which a significant functional activity of P-gp is registered. This induction does not occur in the cells with no detectable P-gp activity (THP-1 suspension cells). This indicates the presence of different mechanisms of RIF influence on MDR1, which can be used to develop a strategy for P-gp inhibition in inflammatory macrophages.Conclusion. Given the key role of macrophages in tuberculosis, further evaluation of MDR1/P-gp in the surgical material of patients with pulmonary tuberculosis is necessary, which makes it possible to draw a conclusion that it is necessary to develop and apply drug strategies aimed at blocking the functional activity of P-gp and choosing more effective anti-tuberculosis therapy regimens.